2006
DOI: 10.1002/bdd.504
|View full text |Cite
|
Sign up to set email alerts
|

Rat strain differences in stereospecific 2‐oxidation of RS‐8359, a reversible and selective MAO‐A inhibitor, by aldehyde oxidase

Abstract: Aldehyde oxidase catalysed 2-oxidation activity of the (S)-enantiomer of RS-8359, a selective and reversible monoamine oxidase A (MAO-A) inhibitor, was investigated in liver cytosolic fractions from ten rat strains. Remarkably large strain differences were observed with approximately a 230 variation between the highest activity in the Wistar-Imamichi strain and the lowest activity in the Slc:Wistar strain. The activities of Crj:SD and Slc:SD strain rats were considerably low, and that of the F344/DuCrj strain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
11
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
3
11
0
Order By: Relevance
“…The genetic variation in aldehyde oxidase was also reported by the electrophoresis method (Kunieda et al, 1999). Similar to those reports, we observed remarkable species differences and rat strain differences in the metabolism of the (S)-enantiomer of RS-8359 Sasaki et al, 2006). During the study of rat strain differences in the 2-oxidation activity of RS-8359, we were aware of the individual variations in Donryu rats, as shown in Wistar rats (Gluecksohn-Waelsch et al, 1967) and Sprague-Dawley (SD) rats (Beedham, 1998).…”
supporting
confidence: 89%
See 1 more Smart Citation
“…The genetic variation in aldehyde oxidase was also reported by the electrophoresis method (Kunieda et al, 1999). Similar to those reports, we observed remarkable species differences and rat strain differences in the metabolism of the (S)-enantiomer of RS-8359 Sasaki et al, 2006). During the study of rat strain differences in the 2-oxidation activity of RS-8359, we were aware of the individual variations in Donryu rats, as shown in Wistar rats (Gluecksohn-Waelsch et al, 1967) and Sprague-Dawley (SD) rats (Beedham, 1998).…”
supporting
confidence: 89%
“…A recent study by Sasaki et al (2006) revealed the low 2-oxidation activity of the (S)-enantiomer in the SD strain. The amino acid sequences of aldehyde oxidase of female SD rats have 1332 of 1333 identities to those of the Donryu PM rats, and both have 110Ser and 852Val sequences.…”
Section: Itoh Et Almentioning
confidence: 99%
“…18,19) The main metabolic pathway of the compound is the AO-catalyzed 2-oxidation on the pyrimidine ring of the molecule. Similar to many reports on AO, we observed a remarkable species differences, [20][21][22] a large strain difference in rat, 23) and an individual difference in Donryu strain rat 24) in the 2-oxidation activity. Further, we reported that a minor 130 kDa subunit in addition to a 150 kDa subunit was observed in the sodium dodecyl sulfatepolyacrylamide gel electrophoresis (SDS-PAGE)/Western blot analysis of monkey and human AO but not in rat AO.…”
Section: )supporting
confidence: 90%
“…15) In addition, large rat strain differences in AO have been reported for benzaldehyde 16) and methotrexate, 17) and even the existence of striking variations in AO activity has been noted in Sprague-Dawley rats 18) and Wistar rats. 19) We also observed phenomena related to species differences, 20,21) rat strain differences, 22) and rat individual differences 23) in the metabolism of RS-8359, which is a selective and reversible MAO-A inhibitor [24][25][26] and has been developed as an antidepressant. 27,28) AO is a homodimer with a subunit molecular mass of approximately 150 kDa.…”
mentioning
confidence: 82%